Adapting, piloting and evaluating complex public health interventions: lessons learned from the Nurse–Family Partnership in Canadian public health settings - Jack, S. M. (Health Promot Chronic Dis Prev Can, 2015)
INTRODUCTION: The Nurse–Family Partnership (NFP) is a home-visit program for young and first-time, socially and economically disadvantaged mothers. Evidence from three United States randomized controlled trials (RCTs) on the effectiveness of this intervention at improving pregnancy outcomes, improving child health and development, and increasing maternal economic self-sufficiency is robust. However, the effectiveness of the NFP in Canada, with its different health and social care context, needs to be determined. The purpose of this article is to describe the complex process for moving the NFP from the research arena to full implementation in Canada. METHODS: This process of evaluation in Canada includes (1) adapting the intervention; (2) piloting the intervention in small-scale feasibility and acceptability studies; and (3) conducting an RCT and process evaluation through a study called the British Columbia Healthy Connections Project (BCHCP). This large-scale evaluation also creates an opportunity to expand the NFP evidence base by conducting an additional study to examine potential biological mechanisms linking intervention and behavioural outcomes in children. RESULTS: Adaptation of the NFP home-visit materials is a continuous process. A pilot project determined that it was feasible to enrol eligible women into the NFP. This pilot also determined that, in Canada, it was most appropriate for public health agencies to implement the NFP and for public health nurses to deliver the intervention. Finally, the pilot showed that this intensive home-visit program was acceptable to clients, their family members and health care providers. Through the BCHCP, the next steps—the RCT and process evaluation—are currently underway. The BCHCP will also set the foundation for long-term evaluation of key public health outcomes in a highly vulnerable population of families.